Reliability and failure behavior of CAD-on fixed partial dentures. Issue 5 (May 2016) - Basso, G.R.; Moraes, R.R.; Borba, M.; Duan, Y.; Griggs, J.A.; Bona, A. Della
Highlights: This study evaluates the reliability of ceramic fixed partial dentures prepared using the CAD-on technology. This study tested the hypothesis that cyclic fatigue influences the reliability and failure behavior of the FPDs when compared to fast fracture testing. Porcelain chipping was the predominant (60%) mode of failure for FPDs tested in fast fracture and connector failure was predominant (67%) under fatigue. When chipping and connector fracture data were analyzed separately, the β values were 7.9 and 2.9. The test method (fast fracture or fatigue) significantly influenced the reliability of FPDs fabricated using the CAD-on technique, but it did not influence their failure behavior. Abstract: Objectives: To estimate the reliability and failure behavior of fixed partial dentures (FPDs) fabricated using the CAD-on technique. Methods: FPDs ( n  = 25) were fabricated using a CAD/CAM system: IPS e.max ZirCAD – Crystall./Connect and IPS e.max CAD (Ivoclar). The restoration type ("three-unit bridge") and design method ("multilayer") based on Biogenerics were used. Framework and porcelain structures were united using a fusion ceramic (Crystall./Connect, Ivoclar). Mechanical fatigue was tested in a servohydraulic load frame machine at a cyclic loading (frequency: 2 Hz; load ratio: 0.1). Based on previous data from specimens tested in fast fracture, three different stress profiles were used. The lifetime data were analyzed using an inverse power law-Weibull cumulative damage model (ALTA PRO, Reliasoft). All failed specimens were examined under a field emission scanning electron microscope. Results: Porcelain chipping was the predominant (60%) mode of failure for FPDs tested in fast fracture and connector failure was predominant (67%) under fatigue. For fast fracture data, the Weibull modulus ( β ) of FPDs was 7.8 combining the two failure modes. When chipping and connector fracture data were analyzed separately, β values were 7.9 and 2.9. For the step stress fatigue test, β values were lower than estimated using fast fracture, being 1.6 for connector fracture and 1.3 for porcelain chipping. Significance: The test method (fast fracture or fatigue) significantly influenced the reliability of FPDs fabricated using the CAD-on technique, but it did not influence their failure behavior.